2017
DOI: 10.1016/j.jsams.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Controlling coaching and athlete thriving in elite adolescent netballers: The buffering effect of athletes’ mental toughness

Abstract: This study extends past work and theory to show that mental toughness may enable athletes to counteract the potentially deleterious effect of controlling coach interpersonal styles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 24 publications
0
28
1
1
Order By: Relevance
“…In the specific context of our study, controlling styles and stricter approaches to exercise are common in the area of PE [51]; therefore, it is possible that, being used to such approaches, participants in the CG were less affected by them, and more willing to engage in the activities. Additionally, it is suggested that adolescents with a strong and positive mindset may be able to deal with such teaching styles in a better way, reducing or nullifying their negative effects [57]. In our sample, students from both EG and CG showed very high levels of psychological wellbeing and self-esteem, at the same time as they had very low stress and anxiety.…”
Section: Physical Fitnessmentioning
confidence: 71%
“…In the specific context of our study, controlling styles and stricter approaches to exercise are common in the area of PE [51]; therefore, it is possible that, being used to such approaches, participants in the CG were less affected by them, and more willing to engage in the activities. Additionally, it is suggested that adolescents with a strong and positive mindset may be able to deal with such teaching styles in a better way, reducing or nullifying their negative effects [57]. In our sample, students from both EG and CG showed very high levels of psychological wellbeing and self-esteem, at the same time as they had very low stress and anxiety.…”
Section: Physical Fitnessmentioning
confidence: 71%
“…The motivational mechanisms of the basic psychological needs might over time underpin why some elite junior performers survive and thrive, despite adversity, and why others experience ill‐being and diminished functioning . Both personal and contextual factors are found to influence the motivational functioning of elite junior performers . Yet, few studies based on self‐determination theory (SDT) have investigated personal factors, even though they are likely to influence the perception of and reaction to environmental requests and demands, thereby influencing the satisfaction or frustration of the three basic psychological needs .…”
Section: Introductionmentioning
confidence: 99%
“…The second overarching theme that underpinned the remaining seven themes to 10 promote thriving (viz., actively nurturing and managing a 'family' club culture, considerately 11 treating non-playing squad members, creating an honest and fear-free environment, facilitating enjoyment, decreasing player turnover rate, establishing a joint team and club goal, and fostering player development), was establishing a connection between the players, the coaching staff and the club. Previous research from D. J. and Gucciardi et al (2017) has highlighted the importance of coach support and coach behaviors with regards athlete thriving; however, the present study is the first to emphasize players' connections to the club/organization. One mechanism that may explain why these relationships promote thriving is the trust created by the bonds (see, Carmeli & Spreitzer, 2009).…”
Section: Discussionmentioning
confidence: 57%
“…Gucciardi, Stamatis, & 18 Ntoumanis, 2017) exist that have explicitly examined proponents of BPNT and thriving. 19 Drawing on a conceptualization of thriving from the work literature (see, Spreitzer et al, 20 2005), Gucciardi et al (2017) found that controlling coach behaviors (e.g., controlled use of 21 rewards, negative conditional regard) were inversely related with experiences of vitality and 22 learning. Using an alternative conceptualization where thriving was indexed by levels of 23 1 It is important to highlight that some evidence also exists to suggest reciprocity in the relationships between need support, need satisfaction/frustration, motivation, and well-being (see, Martinent, Guillet-Descas, & Moiret, 2015;Stenling, Lindwall, & Hassmén, 2015).…”
Section: Sports Performers' Perspectives On Facilitating Thriving In mentioning
confidence: 99%